PENGARUH PENGENCERAN DAN PENGADUKAN LIMBAH DAPUR DAERAH BULUSAN (STUDI KASUS RASIO C/N 17 : 1) TERHADAP PENINGKATAN PRODUKSI BIOGAS DENGAN MENGGUNAKAN EKSTRAK RUMEN SAPI SEBAGAI STARTER - Pradana Sahid Akbar; Irawan Wisnu Wardhana; Sudarno Sudarno (Jurnal Teknik Lingkungan, 2013)
Soaring oil prices affect economic activity in the world, including Indonesia, it would encourage the government to develop renewable energy including biogas. Kitchen wastes has the potential to be a source of renewable energy, namely biogas. Waste food scraps and kitchen activities in sufficient quantities of the restaurants in the area were collected Bulusan, was treated like refinement and homogenization, the extract phase and its substrates include cattle as a source of rumen anaerobic bacteria into the reactor with the addition of water and stirring as a variation. From the results it is concluded, that the addition of water and stirring affect the amount of gas produced. It is known that waste as much as 150 ml of water is added, is able to produce more gas volume than others. In the study indicated a decrease and an increase in gas production. This is due to the formation of gas phase occurs, starting from the stage of hydrolysis, acidogenesis, acetogenesis, and methanogenesis.